Perubahan Sosial Terhadap Lingkungan Masyarakat Dan Perkembangannya: Urbanisasi Dan Teknologi - Makhdum Rosyidi Al’Alim; Meita Dwi Mukhlishotul Azizah; Andhita Risko Faristiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Changes in society will continue for as long as people interact with one another. The phenomenon of urbanization is one form of social change. This is because of geographical, biological, economic, and cultural factors, as well as shifts in social norms, influenced social change. Social change cannot be viewed solely from one perspective because it can result in shifts in numerous social society sectors. This indicates that social change will always occur within society as a whole. Naturally, this social change occurs not only as a result of the individuals who wish to change but also as a result of developments in various fields, particularly technology. Based on theories of social change, the author tries to describe the social changes that take place in society. The type research used is field research while the data collection thecnique is carried out by observation and interview. This research was conducted in Sampung village, Sampung district, Ponorogo Regency to know of the reason why people urbaniz and the impact of urbanization on social and environtmental origin. The result of this study concluded that, 1) the reason how people urbanizm because the economic case, geographical, population compesition, ideology, biological, and new discoveries, 2) the impact of urbanization can improve the economic case and the spread of technology on the other hand it also results in a redaction in agricultural land and social tempest within the family.